Is Boomtown Growth Associated with Crime in Suburban Areas?: Examining the Importance of Rapid Population Growth and Neighborhood Change for Crime in Frisco, Texas - Barton, Michael S. (American journal of criminal justice, 2024)
A substantial body of research has documented the consequences of rapid population growth for crime, but most of this literature focused on population growth in major cities during the first half of the twentieth century or on boomtown growth in rural areas since the 1970s. The findings of both literatures helped to identify important correlates and consequences of rapid population growth, but neither body of research engages with suburban areas in which approximately half of the United States population currently live. The current study examines the relationship of rapid population growth with levels of violent and property crime in one of the fastest growing suburban areas in the United States, Frisco Texas. The results indicate rapid population growth was not associated with changes in crime at the city level, but neighborhood level analyses suggest crime may became more concentrated in certain areas. Longitudinal regression analyses also reveal that many commonly assessed correlates of crime may operate differently in suburban areas than do in urban areas.